STUDY OF THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND FAMILY INCOME WITH STUNTING INCIDENCE IN CHILDREN AGED 2-5 YEARS - Ikhsan Kaloko; Marniati Marniati; Itza Mulyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Parenting patterns and family income have a major influence on the incidence of edits in children aged 2-5 years. The problem is the high number of stunting cases in the festive sub-district, reaching 58 children who are stunted. The purpose of this study was to examine the relationship between parenting patterns and family income with incidence. Research method This type of research is analytic with a cross-sectional design, while the sample is 58 respondents, analyzed by Univariate and bivariate which is then tested with Chi-Square. This research was conducted in December 2021 in the Gunung Meriah sub-district, Aceh Singkil district. The results showed that based on the results of the chi-square test, a value was obtained (P.Value 0.002 <α 0.05) so that it could be described that there was a significant relationship between Parenting Patterns and Stunting Incidents. Furthermore, there is a relationship between family income and the incidence of stunting, where the results of the chi-square test obtained a value (P.Value 0.012 <α 0.05). The conclusion, along with the results of this research study, proved that there was a relationship between parenting and family income with the incidence of stunting as evidenced by the P-value < 0.05. Suggestions for mothers to increase parenting efforts for their children, even though family income is not sufficient to meet the needs for nutritious food for children, try to keep them fulfilled.